PENGARUH KOMPETENSI DAN MOTIVASI TERTHADAP PRODUKTIVITAS KERJA KARYAWAN LOTTE SHOPPING INDONESIA PASAR REBO - Bella Astalia; Arry Dwi Syahputra (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
This study aims to analyze the effect of competence and work motivation on the work productivity employees of PT Lotte Shopping Indonesia Pasar Rebo. This study uses a quantitative approach. The population in this study were employees of Lotte Shopping Indonesia Pasar Rebo. The sampling technique used is simple random sampling. The data collection technique used a questionnaire that had been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression test and simple regression test. The results of this study indicate that simultaneously and partially competence and work motivation have a positive and significant influence on the work productivity employees of PT Lotte Shopping Indonesia Pasar Rebo.